Triggering Postural Movements With Virtual Reality Technology in Healthy Young and Older Adults: A Cross-Sectional Validation Study for Early Dementia Screening - Imaoka, Yu; Saba, Nadja; Vanhoestenberghe, Anne; de Bruin, Eling D. (Frontiers in Medicine, 2020)
With the ultimate aim of early diagnosis of dementia, a new body balance assessment system with integrated head-mounted display-based virtual reality (VR) has been developed. We hypothesised that people would sway more in anterior-posterior (AP) direction when they were exposed to a VR environment where we intentionally provoked movements in forward and backward directions. 14 healthy older adults (OA) (73.14±4.26 years) and 15 healthy young adults (YA) (24.93±1.49 years) were assessed for group differences in sway behaviour. Body sway speed in 22 different conditions with and without VR environments was analysed. Significant differences and large effect sizes were observed in AP sway under the VR environments (OA with P <0.02; effect size>0.61, YA with P <0.003; effect size>0.72) compared to the baseline condition without the VR environments. In addition, significant differences were found between the two groups in AP sway in all test conditions (P <0.01). Our study shows that a VR environment can trigger body sway in an expected direction, which may indicate that it is possible to enhance the sensitivity of balance assessment by integrating immersive VR environments. The result of this study warrants a cross-sectional study in which OA diagnosed with and without dementia are compared on their sway behaviour.